Impact of the GFC on income and earnings in Australia - Chesters, Jenny; Western, John (World Society Foundation, 2012)
The current global financial crisis is a potent reminder of the interconnectedness of the world-economy. Although Australia seems to have escaped the worst of the crisis and avoided a technical recession, falling share prices and returns on investments have impacted upon incomes. In this paper we use longitudinal data collected by the Household Income and Labour Dynamics in Australia (HILDA) Survey (n=9354), to compare both total incomes and the sources of income in 2007 and 2008 to assess the social conditions under which the global financial crisis unfolded.
World Society in the Global Economic Crisis
Keywords: Income & Finance; Employment -- Unemployment; Income, wealth and finances; Labour market; Income & Finance; Employment; Unemployment; Employment and unemployment; Income, wealth and finances